2014
DOI: 10.1002/cssc.201402789
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated Ionomer‐Enveloped Sulfur Cathodes for Lithium–Sulfur Batteries

Abstract: Nafion is known to suppress the polysulfide (PS) shuttle effect, a major obstacle to achieving high capacity and long cycle life for lithium-sulfur batteries. However, elaborate control of the layer's configuration is required for high performance. In this regard, we designed a Nafion-enveloped sulfur cathode, where the Nafion layer is formed on the skin of the cathode, covering its surface and edge while not restricting the porosity. Discharge capacity and efficiency were enhanced with the enveloping configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Furthermore, the value of the corresponding CE remained around 100% during the 160 cycles, indicating the good reversibility and low impact of the shuttle effect in the electrochemical process. The electrochemical performance of our HMMCNT‐S‐50 is thus comparable to many other S‐based cathodes in the literature (see Table S1, Supporting Information), including porous carbon aerogels, microporous bamboo biochar, a conductive MoO 2 matrix, porous carbon nanofibers, and Ni‐metal–organic frameworks (Ni‐MOFs)…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, the value of the corresponding CE remained around 100% during the 160 cycles, indicating the good reversibility and low impact of the shuttle effect in the electrochemical process. The electrochemical performance of our HMMCNT‐S‐50 is thus comparable to many other S‐based cathodes in the literature (see Table S1, Supporting Information), including porous carbon aerogels, microporous bamboo biochar, a conductive MoO 2 matrix, porous carbon nanofibers, and Ni‐metal–organic frameworks (Ni‐MOFs)…”
Section: Resultssupporting
confidence: 60%
“…This research landmark paved the way for the elegant design of Li‐S cathode conformations. In addition, an effective method of using a layer of carbon or polymer to cover the surface of sulfur and its sulfides, which suppresses the dissolution of polysulfide, is very common in Li‐S and S‐containing Li‐ion batteries . Although great achievements have been made in this regard, more challenges must be faced before future applications can be realized, such as the universality of the matrix, the input cost, and the burden caused to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The ratios of Q low /Q high were 2.48, 2.51, 2.67, and 2.74 when the open-circuit intervals were 24, 48, 120, and 240 h, respectively.T he minor increase in the Q low /Q high ratios indicated that the reactionb etween sulfur and remaining loworder polysulfides was tiny compared with that of routine cells (Figure 2c Low self-discharge rate through ion diffusion control In addition to the strategy of directly preventing reactions between high-order polysulfides and the lithium anode by forming an interfacial passivation layer on the anodes, suppressing the diffusion of polysulfide anions to the anode side was expected to be another promising route to reduce self-discharge. In aw orkingl ithium-sulfur cell, the routine shuttleo fp olysulfides is highly dependento nn ot only the "sulfiphilic" affinity and porouss tructures of the cathode, [26] but also on the ion channels in the porouss eparators. [9,27] To prevent the diffusion of polysulfide anionsa nd provide high coulombic efficiency, ac ation-selective Nafion membrane with SO 3 À groups coating the channels was employed.…”
Section: Resultsmentioning
confidence: 99%
“…The method is illustrated here for the case of a lithiated Nafion membrane and its capability to block the transport of iodide ions. Nafion membranes have been successfully used in Li−S cells to block transport of polysulfide species ,,. Iodide has a well‐defined redox behaviour and it is used here as a model for polysulfide redox species, which will be studied in further work.…”
Section: Introductionmentioning
confidence: 99%